Profit Gaining Strategies Through Learning Videos For Physical Education Teachers In Jember Central Region - Sulaiman, Ahmad; Apriliyanto, Rizki; Kusuma Ningtyas, Yoga Dwi Windy; Ramadhani, Dyanisyaf (Journal Of Humanities Community Empowerment, 2024)
The COVID-19 pandemic has made the teaching and learning process carried out remotely. One way is by making learning videos. Based on the results of the situation analysis, several problems were found, namely: (1) Physical Education, Sports and Health (PJOK) teachers do not understand and are not skilled in making learning videos independently, (2) PJOK teachers do not have knowledge about how to increase profits from learning videos. Based on the identification of partner problems and the results of discussions between researchers and partners, solutions that can be offered include (1) training in making PJOK learning videos, and (2) introduction to YouTube channels to publish learning videos that have been made. The service method is carried out in three stages. First, preparation, including situation analysis, discussions with partners regarding the main priorities that are resolved and determining the schedule for implementing the service. Second implementation, the service is carried out with a demonstration method by the service team followed by direct practice by PJOK teachers. Third evaluation, carried out aims to see the extent of the success of the programme. The results of this service activity include: (1) training activities are carried out smoothly through preparation, implementation, and evaluation steps, (2) training activities have an impact and positive response from participants, (3) Participants understand that Microsoft Power Point can make or edit learning videos, and (4) participants understand that learning videos uploaded to YouTube channels can get profit.